Potential and Efforts to Increase Competitiveness Creative Industries in Banda Aceh - Ayuni, Devi; Utomo, Mohammad Noor; Safitri, Julia; Pujiwati , I (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
Banda Aceh, which was recognized as a